1967
DOI: 10.1254/jjp.17.683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol in Experimental Auricular and Ventricular Arrhythmias

Abstract: In view of a recent report that ethanol converted strophanthidin-induced ventricular tachycardia to normal sinus rhythm (1), it was of interest to investigate the effect of ethanol in other experimental cardiac arrhythmias, the underlying mechanisms of which are seemingly different from those provoked by digitalis.Atrial fibrillation was produced according to the method described by Schallek (2) in 6 pentobarbitaliz ed (30 mg/kg i.v.) dogs by the topical application of 5% acetylcholine on the sinus node.Ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Using canine models, Nguyen et al (1987) observed that alcohol caused vasodilation, negative inotropic effect, and atrial antiarrhythmic effect. Madan and Gupta (1967) also observed alcohol atrial and ventricular antiarrhythmic effect in canine models.…”
Section: Electrophysiological Effects Of Ethanol In Experimental Studiesmentioning
confidence: 75%
“…Using canine models, Nguyen et al (1987) observed that alcohol caused vasodilation, negative inotropic effect, and atrial antiarrhythmic effect. Madan and Gupta (1967) also observed alcohol atrial and ventricular antiarrhythmic effect in canine models.…”
Section: Electrophysiological Effects Of Ethanol In Experimental Studiesmentioning
confidence: 75%
“…Moreover, the ad libatum consumption of 10% ethanol during induced audiogenic stress partially blocked stress-related biochemical changes and completely inhibited cardiac hypertrophy [19]. The acute administration of ethanol to anesthetized dogs is capable of suppressing ventricular arrhythmias produced by coronary ligation, cardiac glycoside intoxication, or elevation of the fibrillation threshold to electrical stimulation [20][21][22][23]. A similar elevation of the atrial fibrillation threshold has also been demonstrated [24].…”
Section: Figurementioning
confidence: 87%
“…In particular, Gilmour et al [16] demonstrated in an anesthetized dog model, that ethanol blunted electrocardiogram changes induced by ischemia and the incidence of ventricular fibrillation induced by a rapid stimulation. Anti-fibrillatory effects of ethanol have also been reported [23,28]. Finally, cardio-protective effects (i.e., infarct size) of ethanol during ischemia and reperfusion/reoxygenation have been shown in anesthetized guinea pig and rat models [2,30], isolated perfused rat hearts [2] and cultures of neonate rat cardiomyocytes [40].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that acute ethanol administration suppresses ventricular tachyarrhythmias following coronary artery ligature or digitalis intoxication [23,29] and increases ventricular and auricular fibrillation thresholds [21,22]. In particular, Gilmour et al [16] demonstrated in an anesthetized dog model, that ethanol blunted electrocardiogram changes induced by ischemia and the incidence of ventricular fibrillation induced by a rapid stimulation.…”
Section: Introductionmentioning
confidence: 99%